IN VITRO CYTOTOXIC ACTIVITY OF ISOLATED COMPOUNDS FROM VIBURNUM PUNCTATUM BUCH-HAM EX D. DON - Alex, A. Renjith; Ilango, K. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The main aim of the study was to screen the isolated compounds of Viburnum Punctatum for its in vitro anticancer activity and its percentage viability against HCT 15 (Human Colon Cancer Cells) Cell lines. Methods: Pet ether, Chloroform, Methanol and Aqueous extracts was prepared and assayed for the presence of phytochemicals. Two compounds were isolated from the methanol extract of Viburnum Punctatum by column chromatography such as ME1 (Quercetin) and ME2 (Kaemferol-3-glycoside) characterised by UV, IR, MS, 1H NMR and 13C NMR. The above isolated compounds were subjected to in vitro anticancer activity on HCT 15 cell lines was evaluated by Micro culture Tetrazolium (MTT) assay. Results: ME1 showed significant cytotoxic activity than the ME2 on HCT 15 cells with a percentage viability of 54.60 and 67.18 in the concentration of 10Âµg/ml and 50Âµg/ml respectively. Conclusion: On the basis of obtained results, ME1 and ME2 isolated from a methanolic extract of Viburnum Punctatum represent a new group of cytotoxic against HCT 15 Cell lines.